PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN IPHONE DI JAKARTA SELATAN - Kania Junita Syaputri (2013)
This study aims to determine the effect of brand image, Quality of product, and purchase decisions. The data used are the primary data and data processing is done using spss 21.0. Variable under study consist brand image, quality of product and purchase decision. The analysis used to test the study was multiple regression. With the help of the SPSS 21.0 Method of sampling in this study is a non probability sampling with a purposive sampling method. Variable and can be interpreted brand image has a greater influence on purchase decisions, when compared with the quality of the product.